An annotated checklist of Echinodermata of Montenegro (the south Adriatic Sea) - Kašćelan, Slavica; Mandić, Sreten; Radović, Ivica; Krpo-Ćetković, Jasmina (Zootaxa, 2009)
Published literature on the echinoderms of Montenegro (the south Adriatic Sea) is still very scarce. As a baseline for future studies that will enhance the knowledge of this fauna, we have compiled a checklist combining the existing published data with original data from a recent research. The checklist of the echinoderm fauna of the Montenegrin part of the south Adriatic Sea includes 57 species, grouped into 39 genera and 30 families, of which one crinoid (Crinoidea), 18 asteroids (Asteroidea), 9 ophiuroids (Ophiuroidea), 15 echinoids (Echinoidea), and 14 holothurians (Holothuroidea), which makes 56.4% of the species recorded so far in the Adriatic Sea, and 37.0% of the current total number of Mediterranean echinoderms. Ten recorded species are Mediterranean endemics, and two are Mediterranean subendemics. Six species are new for the fauna of Montenegro.